The relationship between CD34+ stem cell dose and time to neutrophil recovery in autologous haematopoietic stem cell recipients—A single centre experience. Issue 4 (August 2018) - Nath, Karthik; Boles, Rachael; McCutchan, Andrew; Vangaveti, Venkat; Birchley, Andrew; Irving, Ian
Abstract: A retrospective, observational study was performed of 112 patients who underwent autologous haematopoietic stem cell transplantation (ASCT) to determine the relationship between CD34+ stem cell dose and neutrophil engraftment. Importantly, a novel approach to more accurately calculate time to neutrophil engraftment was employed. The results demonstrated that a higher CD34+ stem cell dose was associated with faster neutrophil recovery (P < 0.05). CD34+ stem cell dose using actual and ideal patient body weight were both equally predictive of neutrophil engraftment as were absolute and viable CD34+ measurements. The clinical implications for this relationship are limited with an increase in CD34+ stem cell dose by 1 × 10 6 /kg reducing the neutrophil engraftment time by only 3 h and 50 min. The median time to neutrophil recovery was 217 h (9 days and 1 h) and this relatively early engraftment time may be related to an early initiation of granulocyte colony-stimulating factor (G-CSF) on day +1 post-transplant. Female patients engrafted 17 h faster than their male counterparts on multi-variate analysis (P < 0.05). Conditioning chemotherapy, bacteraemia, G-CSF dose/kg body weight and increasing age had no impact on time to neutrophil recovery.